Metod Dakwah dalam Pengislaman di Sabah (Sebelum Era Penguasaan British Crown Colony): Method of Da’wah in the Islamisation in Sabah (Before the Era of British Crown Colony) - Borham , Abd Hadi; Abdullah, Wahyu Hidayat; Abdul Rahim, Mohamad Marzuqi (Jurnal Usuluddin, 2021)
Da’ie is an important group in the spreading of Islam during the period of sultanate of Brunei and Sulu before British Colony Era. The domination of sultanates has given a positive impact to the spread of da’wah in Sabah (known as North Borneo). The da’i have succeeded to bring a harmonious spiritual need among the locals in Sabah. Islamisation has encouraged comprehensive way of life from legal, economy and politic aspects. This dynamic nature is shown through the effort of Islamisation. It can be seen with the acceptance of Islam from the local community of Sabah (North Borneo); who lived in east coast through the influence of Sultanate of Sulu and flourishing in the west coast of Sabah through the Sultanate of Brunei. Therefore, this study aims to identify the da’wah methods that are a factor to Islamization in Sabah. The design of this study is a literature review with using content analysis of the materials on the study topic. The findings show that there are five methods of da’wah that were highlighted in Islamization in Sabah before the British era. It is an adaptation of the preacher to local life, approaching the ruling class, through marriage and through trade activities, and the factor of the superiority of the sufi preachers.